Prediction of thermal conductivity of 93W–Ni–Fe alloys in sintering process based on finite element analysis - YIN Gang; PAN Qian; ZHAO Teng; YIN Haiqing; WANG Yongwei; QU Xuanhui; XIONG Ning (Fenmo yejin jishu)
Thermal conductivity is an important thermophysical parameter required for the numerical simulation of constitutive equations. The existing thermal conductivity measurement equipment and methods cannot measure the thermal conductivity of refractory metals during high temperature sintering. Based on the prediction model of 93W–Ni–Fe refractory metals with the PixelMapPaint method, the thermal conductivity of 93W–Ni–Fe alloy billets formed by cold isostatic pressing was predicted at different temperatures during the sintering process, and the thermal conductivity was verified by laser flash method. The results show that, when the sintering temperature is 1100 ℃ or below, the prediction accuracy of 93W–Ni–Fe thermal conductivity is high, which is in good agreement with the experimental results with the average relative error of ±2.15%, indicating the reliability of the finite element method for thermal conductivity prediction. When the sintering temperature is higher than 1100 ℃, the actual measurement of thermal conductivity is invalid, and the calculated values by finite element method can be used as the reference to make up for the deficiency of the experimental measurement.